2014
DOI: 10.1099/vir.0.061721-0
|View full text |Cite
|
Sign up to set email alerts
|

The PB2 E627K mutation contributes to the high polymerase activity and enhanced replication of H7N9 influenza virus

Abstract: Human infection by H7N9 influenza virus was first identified in China in March 2013. As of 12 August 2013, a total of 135 documented cases with 44 fatalities had been reported. Genetic and laboratory analyses of the novel H7N9 viruses isolated from patients indicate that these viruses possess several polymerase gene mutations previously associated with human adaptation and potential pandemic capabilities. However, the function of these mutations in the emergence and pathogenicity of the viruses is not well kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
70
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(80 citation statements)
references
References 33 publications
(40 reference statements)
5
70
0
1
Order By: Relevance
“…The mammalian-signature mutation PB2-627K, found in the novel human H7N9 viruses, has been associated with virulence and transmissibility of zoonotic highly pathogenic H5N1 lineage viruses (26)(27)(28). Recent studies using different virus isolates also strongly suggested that the PB2-627K contributes to replication and virulence of H7N9 virus in a mouse model (46,47). Although the PB2-K627E substitution reduced viral polymerase activity in both human and porcine cells as anticipated (Fig.…”
Section: Discussionmentioning
confidence: 87%
“…The mammalian-signature mutation PB2-627K, found in the novel human H7N9 viruses, has been associated with virulence and transmissibility of zoonotic highly pathogenic H5N1 lineage viruses (26)(27)(28). Recent studies using different virus isolates also strongly suggested that the PB2-627K contributes to replication and virulence of H7N9 virus in a mouse model (46,47). Although the PB2-K627E substitution reduced viral polymerase activity in both human and porcine cells as anticipated (Fig.…”
Section: Discussionmentioning
confidence: 87%
“…During the three waves, a reduced number of human H7N9 viruses retained the residue with 186G or 226Q. The majority of human origin H7N9 viruses of each wave acquired PB2-E627K, which increased viral pathogenicity in mice (17)(18)(19). Of note, almost all of the human-or avian-origin H7N9 viruses possessed the I368V mutation in PB1 protein, which would increase the H5N1 viral transmissibility in ferrets (20).…”
Section: Resultsmentioning
confidence: 99%
“…Genetic comparison of human and poultry H7N9 isolates has identified mammalian adaptive mutations; in particular, many of the human H7N9 isolates contained the well-established mammalian adaptive signature K627 or N701 in the PB2 protein, as opposed to the E627 or D701 signature found in avian H7N9 isolates (7,8,10,11). It is known that the E627K substitution, which confers increased viral replication and transmissibility in mammalian hosts (12)(13)(14)(15)(16)(17)(18), may emerge during the viral replication and adaptation inside human hosts, as seen in the Dutch H7N7 human case in 2003 (19,20). However, the relative fitness of E627 and K627 during the avianmammalian interspecies transmission of the H7N9 viruses is not fully characterized.…”
mentioning
confidence: 99%